PENGENDALIAN LEVEL AIR PADA MINIATUR PLTA MENGGUNAKAN DISTRIBUTED CONTROL SYSTEM YOKOGAWA - Kukuh Nur Aji; Muhammad Aziz Muslim; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2019)
PLTA adalah pembangkit yang mengandalkan energi potensial dan kinetik dari air untuk menghasilkan energi listrik. PLTA bersumber dari bendungan atau waduk, pengoperasian waduk bertujuan membuat keseimbangan antara volume tampungan, debit inflow dan outflow. Aturan umum dalam simulasi waduk adalah air waduk tidak boleh turun di bawah tampungan aktif dan air waduk tidak dapat melebihi batas atas tampungan aktif. Penelitian ini difokuskan pada pengendalian level air pada rancang bangun miniatur PLTA menggunakan DCS (Distributed Control System) Yokogawa Centum VP. Respon sistem dengan setpoint 95% dan histeris 2% pada nilai 95,86% dan 93,79% memiliki lebar fluktuasi 3,51% dan frekuensi  0.033Hz. Hasil dengan setpoint 95% dengan satu valve mati dikarenakan sensor arus satu terbaca mati sehingga mendapat histerisis 2% pada nilai 95,5% dan 93,7% memiliki lebar fluktuatif  3,38% dan frekuensi 0.04Hz. Hasil dengan setpoint 95% dengan dua valve mati dikarenakan sensor arus satu terbaca mati dan sensor dua terbaca mati sehingga pompa akan mati sehingga tidak ada histerisis, lebar fluktuatif dan frekuensi. Respon system dengan valve aktif berada pada setpoint 50% dengan selisih waktu 6,2 menit dengam aktifnya pompa. Respon system dengan valve aktif berada pada setpoint 75% dengan selisih waktu 7,7 menit dengam aktifnya pompa dan selisih dengan aktifnya valve 50% adalah 1,5 menit.   Kata kunci: Distributed Control System (DCS), PLTA, Level, Potensiometer   ABSTRACT Hydropower is a generator that relies on potential and kinetic energy from water to produce electrical energy. Hydropower is sourced from dams or reservoirs, the operation of the reservoir aims to make a balance between the volume of the reservoir, the inflow and outflow discharge. The general rule in simulation of reservoirs is that the reservoir water should not drop below the active reservoir and the reservoir water cannot exceed the upper limit of the active reservoir. This study focused on controlling water levels in miniature PLTA design using DCS (Distributed Control System) Yokogawa Centum VP. System response with a 95% setpoint and 2% hysterics at a value of 95.86% and 93.79% has a wide fluctuation of 3.51% and a frequency of 0.033Hz. Results with a 95% setpoint with one valve turned off because the current sensor one is read to off so that it gets 2% hysteresis at a value of 95.5% and 93.7% has a fluctuative width of 3.38% and a frequency of 0.04Hz. The result with a 95% setpoint with two valves turned off because one current sensor is read to off and the two sensors are read to off so that the pump will die so there is no hysteresis, fluctuating width and frequency. System response with active valve is at 50% setpoint with a difference of 6.2 minutes with active pump. The system response with an active valve is at a 75% setpoint with a difference of 7.7 minutes with the pump active and the difference with the 50% valve activation being 1.5 minutes. Keywords: Distributed Control System (DCS), Hydropower, Level, Potentiometer